The Effect of Social Media Usage on Increasing Sales in Micro, Small, and Medium Enterprises (MSMEs): A Case Study of Cut Nyak Dien Road, Pekanbaru - Maria Pransiska; S. Sukarni (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study used a questionnaire as the data collection technique. Based on the data analysis conducted on the research sample, the results showed that the use of social media platforms, including Facebook, TikTok, and Instagram, had a significant simultaneous effect on increasing sales. This finding is indicated by the significance value obtained from the simultaneous test, which was 0.000 < 0.05. The influence of social media usage on sales growth was 64.5%, indicating that Facebook, TikTok, and Instagram contributed significantly to increasing sales. Meanwhile, the remaining 35.5% was influenced by other factors not examined in this study. The implication of this research is that MSMEs should optimize the use of social media as a promotional tool to improve sales performance.